Penempelan Teritip (Arthropoda) pada Beberapa Jenis Mangrove di Kawasan TAHURA Ngurah Rai Bali - Juniartini, Nyoman Sweet; Watiniasih, Ni Luh; Astiti, Ni Putu Adriani; Wiradana, Putu Angga (Bumi Lestari, 2024)
Mangrove ecosystems are able to support biological and ecological life cycles and provide welfare for coastal communities. Pest outbreaks that attack seedlings to mangrove trees often cause ecological losses throughout the TAHURA Ngurah Rai Bali area. The ecological interactions of barnacle pest species in mangrove ecosystems are very complex and highly detailed studies. There is empirical evidence that the attachment of barnacles is strongly associated with allelochemical compounds produced by mangroves. This study aims to inventory the attachment of barnacles (arthropods) to several types of mangroves in the TAHURA Ngurah Rai area of Bali. This study used a purposive sampling method to pay for the location of the observations. Quadrant transects were used to organize the classification of the mangrove plots, barnacle densities being calculated for each transect. The density of barnacles was calculated on the number of barnacles attached to the mangrove plants, then recorded the types of plants attached, types of barnacles, types of planting and the number of individuals for each mangrove classification. The study showed that barnacles planted most of the mangrove seedlings at all stations, while the classification of tree plots only had barnacles attached at station 3. The number of attachments of Amphibalanus sp. the highest was found at station 3 of the R. mucronata tiller classification of 881 individuals, while no attachment of barnacles was found at all stations for S. alba mangroves. Overall, the attachment of barnacles was higher in R. mucronata tillers and had the potential to reduce their growth productivity in the field. Efforts to control barnacles really need to be done to increase the success of planting mangroves in TAHURA Ngurah Rai, Bali.